1994
DOI: 10.1093/oxfordjournals.bmb.a072873
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol induced cardiovascular disease

Abstract: Although the beneficial effects of mild or moderate ethanol consumption have been implied with respect to coronary artery disease, excessive ethanol consumption can result in alcoholic heart muscle disease (AHMD). The latter is characterized by features consistent with dilated cardiomyopathy with concomitant ventricular dysfunction and histopathological abnormalities. By definition, no other cause for the abnormalities in AHMD is demonstrated, other than excessive alcohol consumption. The metabolic basis of AH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 28 publications
2
34
0
Order By: Relevance
“…The current recommendation from the British Heart Foundation is a maximum consumption of 30 g ethanol per day (Preedy and Richardson 1994). Epidemiological studies have shown the protective effect of modest alcohol consumption on the incidence of cardiovascular diseases which account for the majority of death in Western world (Redmond et al, 2000;Tolstrup et al, 2006).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The current recommendation from the British Heart Foundation is a maximum consumption of 30 g ethanol per day (Preedy and Richardson 1994). Epidemiological studies have shown the protective effect of modest alcohol consumption on the incidence of cardiovascular diseases which account for the majority of death in Western world (Redmond et al, 2000;Tolstrup et al, 2006).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This phenomenon was mainly related to the capability of moderate alcohol levels to lower CHD risk factors like high levels of LDL cholesterol and fibrinogen, and to increase in parallel the levels of cardioprotective HDL cholesterol (1,7,8).…”
mentioning
confidence: 99%
“…Despite the reported cardioprotective effect of low to moderate alcohol drinking [1], the causal role of heavy alcohol drinking for certain cardiovascular diseases has been well documented [2, 3]. Therefore, it is important to screen cardiac patients for alcohol-related problems.…”
Section: Discussionmentioning
confidence: 99%
“…Several epidemiologic studies suggest that moderate alcohol intake decreases the risk of coronary heart disease [1]. Despite the cardioprotective effect of alcohol, long-term excessive alcohol consumption is considered a major cause of heart disease for a significant number of people [2, 3]. Problem drinkers constitute a significant proportion of the patients admitted to the General Hospital, and early detection is important for this group of patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation